Update on conjunctival pathology - Hardeep Singh Mudhar (Indian Journal of Ophthalmology, 2017)
Conjunctival biopsies constitute a fairly large number of cases in a typical busy ophthalmic pathology practice. They range from a single biopsy through multiple mapping biopsies to assess the extent of a particular pathological process. Like most anatomical sites, the conjunctiva is subject to a very wide range of pathological processes. This article will cover key, commonly encountered nonneoplastic and neoplastic entities. Where relevant, sections will include recommendations on how best to submit specimens to the ophthalmic pathology laboratory and the relevance of up-to-date molecular techniques.